2023
DOI: 10.1038/s41598-023-32372-3
|View full text |Cite
|
Sign up to set email alerts
|

Regionally high risk increase for precipitation extreme events under global warming

Abstract: Daily precipitation extremes are projected to intensify with increasing moisture under global warming following the Clausius-Clapeyron (CC) relationship at about $$ 7\% /^\circ {\text{C}} $$ 7 % / ∘ C . However, this increase is not spatially homogeneous. Projections in individual models exhibit regions with subst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Regional and local scale hydroclimate changes in a warming climate might be enhanced by local feedback processes, including changes in moisture transport and mass convergence (Fig 1 ) and other land-atmosphere coupling controls, such as soil moisture [51,52], land-use changes, and water management [34]. Modeling studies indicate that regional to local scale increases in precipitation are closer to Clausius-Clapeyron [9] and might be higher (>10% K -1 ) in certain regions, especially considering extreme events alone [53]. A higher convective available potential energy (CAPE) has been associated with increased extreme precipitation in some regions over land [54].…”
Section: Understanding the Causes Of The Anthropogenic Hydroclimate C...mentioning
confidence: 99%
“…Regional and local scale hydroclimate changes in a warming climate might be enhanced by local feedback processes, including changes in moisture transport and mass convergence (Fig 1 ) and other land-atmosphere coupling controls, such as soil moisture [51,52], land-use changes, and water management [34]. Modeling studies indicate that regional to local scale increases in precipitation are closer to Clausius-Clapeyron [9] and might be higher (>10% K -1 ) in certain regions, especially considering extreme events alone [53]. A higher convective available potential energy (CAPE) has been associated with increased extreme precipitation in some regions over land [54].…”
Section: Understanding the Causes Of The Anthropogenic Hydroclimate C...mentioning
confidence: 99%
“…On a global scale, previous studies revealed that the intensity and frequency of extreme events have increased, and this increase is expected to continue [10,[12][13][14]. However, extreme precipitation events are not spatially consistent so exhibit robust spatial variability while temperature extremes generally exhibit consistent behavior, especially for the frequency, with the global-scale changes [15][16][17]. Therefore, different regional scales reveal different change patterns in extreme climate events, and these variations by region lead to impacts that vary spatiotemporally [6,10,18].…”
Section: Introductionmentioning
confidence: 99%
“…The vertical water vapor change mainly depends on the local water vapor gradient, which is related to the evaporation process from the surface. Therefore, the anomalous moisture vertical gradient convected by climatological vertical advection reveals that this positive precipitation anomaly is more closely related to the water vapor change associated with global warming and increased aerosol emissions(Zhang et al 2020, Allan and Douville 2023, Kotz et al 2023, Martinez and Neelin 2023…”
mentioning
confidence: 99%